Mice with missense and nonsense NF1 mutations display divergent phenotypes compared with human neurofibromatosis type I - Kairong Li; Ashley N. Turner; Min Chen; Stephanie N. Brosius; Trenton R. Schoeb; Ludwine M. Messiaen; David M. Bedwell; Kurt R. Zinn; Corina Anastasaki; David H. Gutmann; Bruce R. Korf; Robert A. Kesterson (The Company of Biologists, 2016)
Neurofibromatosis type 1 (NF1) is a common genetic disorder characterized by the occurrence of nerve sheath tumors and considerable clinical heterogeneity. Some translational studies have been limited by the lack of animal models available for assessing patient-specific mutations. In order to test therapeutic approaches that might restore function to the mutated gene or gene product, we developed mice harboring NF1 patient-specific mutations including a nonsense mutation (c.2041C>T; p.Arg681*) and a missense mutation (c.2542G>C; p.Gly848Arg). The latter is associated with the development of multiple plexiform neurofibromas along spinal nerve roots. We demonstrate that the human nonsense NF1Arg681* and missense NF1Gly848Arg mutations have different effects on neurofibromin expression in the mouse and each recapitulates unique aspects of the NF1 phenotype, depending upon the genetic context when assessed in the homozygous state or when paired with a conditional knockout allele. Whereas the missense Nf1Gly848Arg mutation fails to produce an overt phenotype in the mouse, animals homozygous for the nonsense Nf1Arg681* mutation are not viable. Mice with one Nf1Arg681* allele in combination with a conditional floxed Nf1 allele and the DhhCre transgene (Nf14F/Arg681*; DhhCre) display disorganized nonmyelinating axons and neurofibromas along the spinal column, which leads to compression of the spinal cord and paralysis. This model will be valuable for preclinical testing of novel nonsense suppression therapies using drugs to target in-frame point mutations that create premature termination codons in individuals with NF1.